#Education: The Potential Impact of Social Media and Hashtag Ideology on the Classroom - Ellen Watson (Research in Social Sciences and Technology, 2020)
Common on social media platforms, the hashtag (#) organizes users’ ideas, emotions, and comments. Originally used to create a searchable platform, the hashtag and its ideology present interesting considerations for changes to education. As students using social media today most certainly use hashtags to converse, hashtag-informed teaching could connect education to students’ worlds instead of forcing students to fit into the pre-defined world of education. Prevalent in post-secondary education, K-12 educators have recently begun to integrate social media tools into their classrooms, but what are the pedagogical implications of the ideologies of these tools? In response, this study asked the following question: “How can the hashtag inform the K-12 classroom?” Using a systematic literature review and thematic analysis, this study analyzed eight articles that discussed the use of hashtags with K-12 students. Findings indicated four themes that could inform the alignment of K-12 classrooms with hashtag ideology: encouraging voice and user-generated content, the potential of self-organization, network hetero/homogeneity, and connecting to space without a common physical space. Suggestions are provided as to how classrooms (and education) may consider restructuring to better reflect hashtag ideology, meeting students in their social media-driven world.